THE IMPACT OF INSTRUCTORS ON THE ENHANCEMENT OF STUDENT COGNITION AND CONDUCT - G’ulomqodirova Robiyabonu (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The role of a teacher is far beyond teaching a subject or a lesson. A teacher is responsible for shaping the character and personality of students along with improving their academic performance. As such, teachers hold a crucial role in improving student knowledge and behavior.